Isolation and Culture of Purified Aortic Endothelial Cells Derived from Alpha 1, 3-galactosyltransferase-deficient Pigs - Sun A Ock; Malgum Lim; Yeongji Kim; Imran Ullah; Yurianna Shin; Youngim Kim; Keon Bong Oh; Seongsoo Hwang; Tai-Young Hur; Seunghoon Lee; Gi-Sun Im (The Korean Society of Animal Reproduction and Biotechnology, 2017)
Tissue engineering (TE) has been developed to create functional organs and tissue by combining 3D matrix and cells in vitro. Vascularization and angiogenesis are utmost important for supply of nutrients and oxygen in tissue engineered organs. The present study was performed to isolate and characterize primary endothelial cells (EC) from aorta of alpha 1, 3-enzyme galactosyltransferase knock out (GalT KO) pig, to minimize immune rejection and analyze body immune system for future xenotransplantation studies. Isolation of primary EC from aorta were performed by incubation with dispase for 8-10 min at 37°C. Primary EC were cultured in EC growth medium on different extra cellular matrix (ECM), either collagen or gelation. Primary EC exhibits morphological characteristics and showed positive expressions of EC specific marker proteins i.e. PECAM1, KDR and VWF despite of their ECM surface; however, on collagen based surface they showed increase in mRNA level analyzed by qPCR. Primary EC cultured on collagen were sorted by flow cytometer using KDR marker and cultured as KDR positive cells and KDR negative cells, respectively. KDR positive cells showed dramatically increased in PECAM1 and VWF level as compared to KDR negative cells. Based on the above results, primary EC derived from GalT KO are successfully isolated and survived continuously in culture without becoming overgrown by fibroblast. Therefore, they can be utilize for xeno organ transfer, tissue engineering, and immune rejection study in future.